Do Rotation and Measurement Methods Affect Reliability of Anterior Cruciate Ligament Tunnel Position on 3D Reconstructed Computed Tomography?. Issue 12 (6th December 2019) - Moon, Hyun-Soo; Choi, Chong-Hyuk; Jung, Min; Lee, Dae-Young; Chang, Hsienhao; Kim, Sung-Hwan
Background: The literature has seldom investigated the anterior cruciate ligament (ACL) tunnel position while considering the effect of rotation of 3-dimensional computed tomography (3D-CT) images during measurements. Hypothesis: We hypothesized that (1) measurement of the ACL tunnel position in the femur and tibia through use of 3D-CT is considerably influenced by rotation of the 3D model and (2) there exists a reliable measurement method for ACL tunnel position least affected by rotation. Study Design: Controlled laboratory study. Methods: The 3D-CT images of 30 randomly selected patients who underwent single-bundle ACL reconstruction were retrospectively reviewed. For femoral tunnel assessments, rectangular reference frames were used that involved the highest point of the intercondylar notch and outer margins of the lateral femoral condyle (method 1), the highest point of the intercondylar notch and outer margins of the lateral wall of the intercondylar notch (method 2), and the lowest point of the intercondylar notch and outer margins of the lateral femoral condyle (method 3). For tibial tunnel assessments, rectangular reference frames with the cortical outline at the articular surface of the tibia (method A) and the cortical outline of the proximal tibia (method B) were used. For both femoral and tibial assessments, the tunnel positions at 5°, 10°, and 15° of rotation of the 3D model were compared with that at a neutral position. Results: The values measured by methods 1 and 3 showed significant differences at greater than 5° of rotation compared with the value at the neutral position, whereas method 2 showed relatively consistent results. However, the values measured with both methods A and B showed significant differences at greater than 5° of rotation compared with the value at the neutral position. Conclusion: The tunnel position on 3D-CT images was significantly influenced by rotation during measurements. For femoral tunnel position, measurement with a reference frame using the lateral wall of the intercondylar notch (method 2) was the least affected by rotation, with relatively consistent results. Clinical Relevance: This study demonstrates that measurement using the lateral wall of the intercondylar notch might be a consistent and reliable method for evaluating the ACL femoral tunnel position considering the effect of 3D-CT image rotation during measurements. However, both methods to measure tibial tunnel position described in this study were similarly affected by rotation.